α2-Antiplasmin, Plasminogen Activator Inhibitor (PAI) and Dilute Blood Clot Lysis Time in Selected Disease States - Cucuianu, Mircea; Knauer, Oliver; Roman, Stefan (Thrombosis and Haemostasis, 1991)
This paper is an attempt to assess the relevance of the inhibitors of fibrinolysis for clot lysis in selected disease states and to discuss the mechanisms leading to acquired abnormal levels of such inhibitors. When compared to 20 control subjects the 30 hypertriglyceridemic patients (14 with type IIb and 16 with type IV) displayed significantly (p <0.001) increased plasma plasminogen activator inhibitor (PAI) activity (221 ± 88% and 290 ± 104% respectively; mean ± SD), moderately (p <0.01) increased α2 antiplasmin (α2AP) level (112 ± 11% and 115 ± 16%) and accordingly an obviously prolonged dilute blood clot lysis time (DBCLT). Neither PAI activity and α2AP level nor DBCLT were significantly different from controls in the 10 patients with hyperlipoproteinemia type IIa. The 18 patients with severe hepatic cirrhosis had low α2AP level (59 ± 19.7%) and accelerated clot lysis, while mean PAI activity (160 ± 87%) was slightly (p <0.05) increased. In the 17 nephrotic patients α2AP was increased (115 ±12%) while PAI activity was similar to controls and DBCLT rather shorter. Two liver secretion enzymes, namely serum Cholinesterase and plasma protein C, were found to be decreased in cirrhotic patients, similar to control values in hyperlipoproteinemia type Ha and obviously increased in nephrotic patients as well as in hypertriglyceridemic subjects. The relevance of PAI and α2AP for clot lysis was considered in relation to data in the literature concerning the behaviour of t-PA and factor XIII. Enhanced hepatic synthesis of protease inhibitors and factor XIII as a possible cause of delayed clot lysis in hypertriglyceridemia was envisaged.